Dinamika Ketegangan Geopolitik, Ukuran Perusahaan, Profitabilitas, dan Return Saham F&B Periode 2020–2025 - Clara Shinta Maharani; Ibnu Aswat; Nella Yantiana (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2026)
Rising geopolitical tensions between 2020 and 2025 have intensified uncertainty in financial markets, potentially affecting stock return movements. This study examines the effects of firm size and profitability on stock returns among food and beverage companies listed on the Indonesia Stock Exchange, while evaluating the moderating role of geopolitical tension in these relationships. Its novelty lies in positioning geopolitical tension as a moderating variable linking firm fundamentals to stock returns within the non-cyclical food and beverage sector. A quantitative approach was applied using panel data regression with Moderated Regression Analysis (MRA), drawing on a sample of 18 companies selected through purposive sampling, which produced 108 panel data observations. The findings show that profitability has a positive and significant effect on stock returns, while firm size shows no significant influence. Geopolitical tension is found to weaken the relationship between firm size and stock returns, but does not significantly moderate the relationship between profitability and stock returns. These results provide empirical evidence on how geopolitical tension moderates the link between firm fundamentals and stock returns in the non-cyclical food and beverage sector.